Microstructure and Mechanical Properties of AM50A Magnesium Alloy Components Prepared by Die Casting and Double Control Forming. (25th June 2014) - Jiang, Jufu; Nie, Xi; Wang, Ying; Yang, Jing
Abstract : The complex motorcycle wheel components of AM50A magnesium alloy had been formed by double control forming and die casting, respectively. The surface quality of components formed by double control forming was much better than die casting parts. When double control forming was used to replace die casting to form motorcycle wheel components, the tensile strength increased from 149.4 MPa to 207.0 MPa and the elongation increased from 5.6% to 10%. The fracture mode was transformed from brittle one of die casting parts to ductile one of double control forming parts. The average grain sizes in the spoke region and the hub region of double control forming wheels were 16 μ m and 20 μ m, respectively, which were smaller than those of die casting components. The matrix phase of the spoke part was α -Mg, the second phase was Mg17 Al12 . A fishbone morphology of the second phase of die casting parts was found in the grain boundaries. The second phase of double control forming parts was like needle or rod presence at the grain boundaries. The thickness and spacing twinning in double control forming components became smaller.